Study of Emerging Trends of E-learning Through Mass Media in Higher Education (ShodhVarta, 2024)
India has one of the largest higher education system in the world, with 1019 University. The COVID-19 paused the entire world and over 1.2 billion children became out of the classroom so there is need of e-learning system which help the students for continue their own study. E-learning accessible 24/7 anywhere, anytime and cost efficient. The study focuses on different form of emerging trends of media like online learning, social learning, artificial learning, flipped learning, blended learning help the learner to connect with best educator in the world. E-learning can also be termed as a network enabled transfer of skills and knowledge, and the delivery of education is made to large number of recipients at same or different times, knowledge can also be shared via the internet which is accessible 24/7 anywhere, anytime. E-learning has bright future in India. Even the people in remote areas are able to get the lectures from best Institutions via E-Learning, but they have to be self-motivated and must have interest to learn.